2017
DOI: 10.17953/1545-0317.15.1.109
|View full text |Cite
|
Sign up to set email alerts
|

The Political Representation of Asian-Australian Populations since the End of White Australia

Abstract: The racial and ethnic landscape in Australia has changed markedly since the beginning of the postwar migration period in which migrants arrived from Europe, and later from Asia in the late 1970s. While Australians with European ancestry have gradually made it into state and federal parliament, there has been less visibility for Australians of Asian descent. This article provides an overview of demographic migration trends and levels of Asian-Australian political representation in state and federal politics, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Despite the gravity of the problem, the literature examining the underrepresentation of visibleminorities (who on account of their name, phenotypical features or skin colour are subject to racial categorisation) is relatively less developed. Extant research has revealed that underlying prejudices and discrimination within political parties make it difficult for ethnic minorities to get ahead (Kwok and Pietsch 2017). The professionalisation of parties and the need to demonstrate loyalty disadvantages newcomers, while geographical dispersal means parties have no incentive to include ethnic minorities (Pietsch 2018).…”
Section: Identifying the Problem As One Of Overrepresentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the gravity of the problem, the literature examining the underrepresentation of visibleminorities (who on account of their name, phenotypical features or skin colour are subject to racial categorisation) is relatively less developed. Extant research has revealed that underlying prejudices and discrimination within political parties make it difficult for ethnic minorities to get ahead (Kwok and Pietsch 2017). The professionalisation of parties and the need to demonstrate loyalty disadvantages newcomers, while geographical dispersal means parties have no incentive to include ethnic minorities (Pietsch 2018).…”
Section: Identifying the Problem As One Of Overrepresentationmentioning
confidence: 99%
“…As a general explanation for the underrepresentation of visible-minorities these reasons are insufficient at best. Research shows that migrants are likely to be more highly educated relative to the general population (Kwok and Pietsch 2017) and that civic engagement is highest among young people from multicultural backgrounds. 18 First-generation Chinese-Australians with poor English participate in political activities more frequently than other groups (Sheppard et al 2020).…”
Section: Addressing Inertia and Incumbency Logjamsmentioning
confidence: 99%
See 1 more Smart Citation